Predicting track and field records in London 2012 Olympic games using gray model - Mollaei, F.; Nejad, M. H. (European Journal of Experimental Biology, 2013)
Gray prediction model is one of the quantitative prediction methods, which was used in this study to predict track and field records in London 2012 Olympic Games. After predicting the records, their accuracy and controllability were investigated sport branches and finally prediction records of2008 Olympic Games were compared with their actual records. This study sought to predict records of track and field branches for men and women in 2012 Olympic Games by gray model. The necessary data were collected via the Internet and, finally, prediction model was tested and investigated in terms of controllability, prediction error and reliability of the results. The research methodology was descriptive and its statistical population included results of all track and field competitions in 26 Olympics Games between 1986 and 2008. Considering the nature of research, the number of samples included track and field records in at least 4 recent Olympic Games. The research tools were observing available documents, using online databases, articles, magazines, newspapers and books in this area. Findings of this study showed that record prediction of 19 branches of track and field competition in 2012 Olympic Games was possible for men and women using gray model. All these predictions were acceptable and controllable. Prediction error of records was not different between men and women. Prediction of records and accuracy and controllability of predicted records in the current and similar previous studies approve the reliability of gray prediction model. The purpose of these predictions is to provide guidelines for decision makers, athletes and even sport fans.